Проблеми правового регулювання провадження у справах про видворення іноземців та осіб без громадянства - Ківалов, Сергій Васильович; Кивалов, Сергей Васильевич; Kivalov, Sergej (Одеса : Юрид. л-ра, 2012)
The article is devoted to the analysis of the current legislation concerning legal regulation of the proceeding in cases connected with deportation of foreigners and persons without a citizenship. Special attention is devoted to the characteristic of the current international agreements, which are obligatory under the assent of Verkhovna Rada of Ukraine, and also to the reveal of collisions between them and the national legislation.
Ківалов С. В. Проблеми правового регулювання провадження у справах про видворення іноземців та осіб без громадянства / С. В. Ківалов // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 7-18.
Keywords: іноземці; особи без громадянства; видворення; правове регулювання; міграція; біженці; иностранцы; лица без гражданства; выдворение; правовое регулирование; миграция; беженцы; foreigners; persons without a citizenship; deportation; legal regulation; migration; refugees